2014
DOI: 10.1021/ef500849z
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Birch Wood Pyrolysis Oils by Ultrahigh-Resolution Fourier Transform Ion Cyclotron Resonance Mass Spectrometry: Insights into Thermochemical Conversion

Abstract: A laboratory-scale reactor was used to produce pyrolysis oils from Finnish silver birch hardwood (Betula pendula). The resulting wood distillates were characterized by ultrahigh-resolution (12 T) Fourier transform ion cyclotron resonance (FT-ICR) mass spectrometry coupled with negative-ion electrospray ionization (ESI). Two different pyrolysis temperatures were tested: 300 and 380 °C (the resulting oil samples were named as Oil-300 and Oil-380, respectively). The detected species were sorted on the basis of he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
55
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(56 citation statements)
references
References 41 publications
1
55
0
Order By: Relevance
“…[18][19][20][21][22][23][24][25][26][27] One of the earliest studies was the work of Smith et al who used orbitrap mass spectrometry coupled with LDI to analyze fast pyrolysis oil from pine wood. 18 They were able to detect 136 oxygen-containing compounds, mostly lignin depolymerization products.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[18][19][20][21][22][23][24][25][26][27] One of the earliest studies was the work of Smith et al who used orbitrap mass spectrometry coupled with LDI to analyze fast pyrolysis oil from pine wood. 18 They were able to detect 136 oxygen-containing compounds, mostly lignin depolymerization products.…”
Section: Introductionmentioning
confidence: 99%
“…While small amount of nitrogen was also observed by elemental analysis in both phases, no nitrogen-containing heteroatom compounds could be identified by ESI FT-ICR MS. However, some previous studies have reported a few, low abundant nitrogen containing species in pyrolysis oils 26,27. In addition, sodiated compounds (O x Na heteroatom class) could be identified from the aqueous phase.…”
mentioning
confidence: 97%
“…Table 2 shows a list of some of the formulas attributed to the O x (x=2-5) class with the same DBE but with an increment of~30.01050 Da due to the loss of a methoxy group (CH 2 O). Such an increment is typical of pyrolysis products generated from lignin biomass [20]. Figure 5 shows the DBE x relative abundance plots for all of the detected Ox classes (x=2-5) for the three bio-oils analyzed.…”
Section: Resultsmentioning
confidence: 91%
“…For instance, Jarvis and co-workers [19] used ESI (−)-FT-ICR MS data to characterize the bio-oil obtained from the pyrolysis of solid biomass, and hundreds of acidic polar compounds were attributed. Kekäläinen and co-workers [20] also characterized hundreds of compounds of Birch wood pyrolysis oils (BWPO) using ESI(−)-FT-ICR MS and primarily observed compounds in the O x (x=2-14) class. Because ESI(−) was used, acidic polar components were assigned, such as acids, phenols, and alcohols.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to petroleum and its derived liquids, FT‐ICR MS has been successfully used for molecular composition analysis of other complex organic mixtures, such as bio‐oils (Jarvis et al, ; Liu et al, ; Kekäläinen, Venäläinen, & Jänis, ; Sudasinghe et al, ; Tessarolo et al, ; Yan et al, ), shale oils (Bae et al, ; Chen et al, ; Jin, Kim, & Birdwell, ; Tong et al, ), humic and fulvic acids (Brown & Rice, ; Kujawinski, Hatcher, & Freitas, ; Kramer, Kujawinski, & Hatcher, ), and biological samples (Brown, Kruppa, & Dasseux, ; Smith et al, ; Barry et al, ), as well as CDLs which will be discussed specifically in the sections below. The application of FT‐ICR MS to the revelation of molecular compositions of chemicals in CDLs has lagged behind that of petroleum and its derived liquids.…”
Section: Class Chemicals Revealed By Ft‐icr Ms In Cdlsmentioning
confidence: 99%